Integrative multi-omics analysis reveals genetic and epigenetic regulatory networks of body weight in the mud crab (Scylla paramamosain) - Qionghui Qin; Weiren Zhang; Meiling Liang; Yijia Shih; Yaodong Zhang; Siyi Zhou; Kewei Huang; Xiaopeng Wang; Haihui Ye (Aquaculture, 2027)

Multi-omics Mendelian randomization and machine learning identify candidate therapeutic targets for Alzheimer’s and Parkinson’s diseases - Xun Li; Lei Zhang; Jinyan Xia; Meiling Zheng; Zhipeng Zhou; Jing Cai (Mammalian Genome, 2026)

An unconstrained implicit stress integration algorithm for the HS model - Xin Zhou; Meiling Jiang; Chun Lei; Cancan Su; Guosheng Wang; Fengwen Lai; Dechun Lu (Computers and Geotechnics, 2026)

Chemical reaction driven interfacial reconstruction of In2O3/S-BiOCl heterojunction with Ag2S quantum dots enables a self-validated fluorescence/photoelectrochemical dual mode nitrite sensing - Jingshu Li; Yuee Zhong; Manqi Li; Jiawei Zhou; Hengwen Tang; Jing Liu; Jianru Tang; Xiaohua Zhu; Youyu Zhang; Meiling Liu (Analytica Chimica Acta, 2026)

A double-platform assay for rapid and on-site detection of chikungunya virus by integrating catalytic hairpin assembly with lateral flow immunochromatography assay - Ruijie Lu; Dawen Chen; Ai Chen; Shuo Ma; Yuming Yao; Yaya Chen; Gulinaizhaer Abudushalamu; Meiling Zhou; Xiao Li; Yue Zheng; Wenjing Lu; Yueqi Wang; et al. (Analytica Chimica Acta, 2026)

Inner Ear Organoids: Recent Progress and Challenges - Yingxinyu Li; Cairong He; Jiayan Liu; Haiqin Zhang; Hongxia Zhang; Zheyu He; Mengyang He; Meiling Chen; Feiyan Zhou; Jie Ding (Stem Cell Reviews and Reports, 2026)

Landsat observation reveals upward trend of surface water temperature in the Three Gorges Reservoir over the past quarter century: divergent effects of climate changes and dam constructions - Han Peng; Botian Zhou; Dongmin Wang; Yue Yuan; Guang Li; Meiling Liu; Ling Wu; Mingsheng Shang (Journal of Oceanology and Limnology, 2026)

An NSGA-III–based predict–optimize–evaluate framework for low carbon land use optimization: A case study of the Yangtze River Delta - Menglin Yu; Jie Tao; Peng Zhang; Meiling Zhou; Beiying Huang; Jie Guo; Jialin Yi (Journal of Environmental Management, 2026)

Bioinspired domed cone-pillar nanoarrays design for robust and low-haze-transparent superhydrophobic quartz glass - Yingying Dou; Yue Fan; Qiongwen Fu; Meiling Tao; Junyin Ouyang; Hongtao Liu; Lin Liu; Yabin Yang; Shilin Huang; Shan Zhou; Xuelin Tian (Chemical Engineering Journal, 2026)

Impacts of vegetation management on pollination network structure and robustness in urban parks: A case study from Beijing Wenyu River Park - Yaxuan Li; Meiling Shu; Chenxi Li; Liwen Liu; Yan Zhou; Lan Wu; Yuyu Wang (Urban Ecosystems, 2026)

Drug-Induced Noninfectious Myocarditis/Pericarditis: A Real-World Pharmacovigilance Study Using the FAERS Database - Shijie Zhao; Weiyi Chen; Chao Tao; Ke Wang; Liuxuan Yang; Ruixiao Li; Meiling Zhou; Jinlu Shang; Xianbin Liu (Cardiovascular Toxicology, 2026)

Decoupling predictors of arbuscular mycorrhizal fungal α- and β-diversity: Plant phylogeny versus functional traits in an alpine artificial grassland of Three-River Source Region - Guoxi Shi; Yingli Ma; Ning Wu; Meiling Guo; Xinchuang Wang; Yongjun Liu; Huyuan Feng; Huakun Zhou; Buqing Yao (Applied Soil Ecology, 2026)

Multi-scenario land use optimization towards carbon neutrality: An integrated predict-optimize-evaluate decision support framework - Menglin Yu; Tao Zhou; Jialin Yi; Wenxu Wang; Meiling Zhou; Jie Tao; Jie Guo (Journal of Cleaner Production, 2026)

Exogenous plant growth-promoting rhizobacteria boosting photosynthetic efficiency via thylakoid lipid restructuring in potato under low-potassium conditions - Xin Zhou; Xin Cheng; Baoyu Fu; Meiling Li; Chao Luo; Haoyang Gong; Hongkun Yang; Jingye Fu; Chengcheng Cai; Kaiqin Zhang; Shunlin Zheng (Plant Science, 2026)

Coupled crack-rainfall mechanism of a retrogressive landslide: field investigation and monitoring in Southwest China - Qiuxiang Huang; Shupeng Li; Meiling Xiong; Chu Zhang; Yan Zhou (Bulletin of Engineering Geology and the Environment, 2026)

Bibliometric analysis of Pseudomonas aeruginosa vaccine development highlighting research status, evolution, and future opportunities - Shiqin Huang; Yi Zhou; Meiling Wu; Xinyan He; Jie Liu; Xinyao Chen; Chunyong Xia; Wen Wu; Ying Fan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Nicking-controlled biosensor: Integrating DNA Walker-RCA circuit with trimetallic nanozyme for aflatoxin B1 detection - Longsheng Jin; YuJing Liu; Wenqing Xia; Meiling Zhou; Ziying Xiao; Jingyu Ge; Xiao Yuan; Qinqiang Zhu; Meisheng Wu (Analytica Chimica Acta, 2026)

Optimal information transmission in a non-Markovian auto-regulatory gene expression system - Zihao Wang; Meiling Chen; Zhenquan Zhang; Xiyan Yang; Tianshou Zhou; Changhong Shi; Jiajun Zhang (BioSystems, 2026)

FeOOH@HAnB catalyst with exposed (211) facet: High stability and new degradation routes for tetracycline - Yingru Huang; Meiling Zhou; Yaping Zhang; Yufeng He; Yuanyuan Xie; Rongmin Wang (Environmental Research, 2025)

Visible light driven highly selective oxidation of HMF coupled with H2 evolution via bimetal-doped synergism on ZnIn2S4 nanosheets - Yachen Hu; Wei Jiang; Zijun Zhang; Qinqin Jiang; Yawen Jiang; Lang Sun; Panjing Xu; Yanling Chang; Chuanqiang Wu; Ziming Fan; Meiling Wang; Zhou Chen; et al. (Chemical Engineering Journal, 2025)

A novel “WRF+AutoML” framework for enhanced heat estimation in urban environments - Meiling Gao; Huifang Li; Fei Chen; Mengzi Zhou; Guijun Yang; Dun Zhu; Dawei Han; Zhenhong Li (Sustainable Cities and Society, 2025)

Long-term nitrogen enrichment affects soil organic carbon fractions through microbial pathways in fluvo-aquic soil - Binggeng YANG; Jiwen CUI; Meiling ZHANG; Kangrui FANG; Chao AI; Tengfei GUO; Shaomin HUANG; Dali SONG; Wei ZHOU (Pedosphere, 2025)

Different responses of cyanobacterial communities to climate change and anthropogenic activities revealed by the 500-year sedimentary record of Lake Daihai - Jing Wang; Hai Xu; Jianghu Lan; Kang’en Zhou; Yunping Song; Jin Zhang; Meiling Yang; Baoli Wang (Anthropocene, 2025)

The behavior of NOM-Cu(Ⅱ)colloids at the goethite interface - Yuekang Chen; Lijuan Zeng; Kai Chen; Meiling Yin; Xiongkai Zheng; Yuting Zhou; Yanping Deng; Jiehong Ye; Zhi Dang; Chuling Guo (Water Research, 2025)

Large-scale mapping and uncertainty assessment of dominant tree species in southern China based on Sentinel-2 time series - Ben Yang; Yuxin Zhao; Junji Li; Meiling Liu; Lei Feng; Botian Zhou; Ling Wu (Journal of Environmental Management, 2025)

Three birds with one stone: a facile superparamagnetic aptasensor for selective capture, dual-mode detection and efficient elimination of methicillin-resistant Staphylococcus aureus - Fengfeng Zhao; Yuming Yao; Shuo Ma; Jiwei Wang; Abudushalamu GuliNaizhaer; Meiling Zhou; Yaya Chen; Xun Gao; Xiaobo Fan; Chen Zhang; Xinglu Jiang; Guoqiu Wu (Chemical Engineering Journal, 2025)

Synergistic enhancement of ionic conductivity and mechanical strength of inorganic hydroxide exchange membranes via orientation engineering for water electrolysis - Qingjie Xi; Wei Wang; Ruixiang Guo; Chenyi Zhao; Xiaofen Liu; Xiaorui Jin; Yongan Yang; Kai-Ge Zhou; Meiling Wu (Chemical Engineering Journal, 2025)

Characteristics and mechanisms of sea (salt) water intrusion in Laizhou City, Shandong Province, China - Linghao Kong; Hongxian Chu; Guohua Hou; Jiao Zeng; Liyuan Zhao; Xiangcai Han; Yachao Li; Faqiao Zhou; Meiling Yin; Xuzhen Zhang (Frontiers in Marine Science, 2025)
Sea (salt) water intrusion is a significant and ongoing geological disaster, and in recent years, it has become a notable concern for Laizhou City, Shandong Province. To identify the characteristics and mechanism of sea (salt) water intrusion in Laizhou City, samples of different types of water bodies (such as seawater, freshwater, slightly brackish water, brackish water, saline water, and brine) were systematically collected from the coastal zone area. The hydrochemical composition and evolution characteristics of the water bodies and the current situation, trends, and causes of sea (salt) water intrusion were analyzed. In 2020, the sea (salt) water intrusion reached 645.76 km 2 (including 151.64 km 2 of serious intrusion area), which is the largest ever recorded. The sea (salt) water intrusion had a strip-sheet distribution. From land to sea, groundwater gradually transitioned from the HCO 3 ·SO 4 ·Cl-Ca type to SO 4 ·Cl-Na·Ca and SO 4 ·Cl-Na types and then evolved to the Cl-Na type. Furthermore, from land to sea, the dominant cations and anions shifted from Ca 2+ and HCO 3 - to Na + and Cl - . The influence of seawater or brine gradually increased, that of Ca 2+ and HCO 3 - gradually decreased; whereas that of Cl - and Na + gradually increased, showing a division zone of freshwater → slightly brackish water → brackish water → saline water → seawater (brine) in the macroscopic territory. The freshwater, slightly brackish water, and brackish water bodies in the study area were controlled by evaporation and concentration processes and rock weathering leaching, whereas the saline water and brine were primarily controlled by evaporation and concentration processes. Groundwater salinity in the study area mainly originates from sea (salt) water intrusion, and locally groundwater salinity mainly originates from mineral dissolution or human activities. In addition, significant cation exchange adsorption occurred in slightly brackish and brackish water. Overall, these results will help to prevent and control seawater intrusions and improve disaster management.

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Development of the novel formulations of perospirone for the treatment of schizophrenia - Zijun Zhang; Famin Ke; Jili Wu; Xiyao Li; Xin Chen; Lanxing Zhang; Pei Jing; Zerong Liu; Zhongbing Liu; Ruilin Lu; Shihua Fu; Meiling Zhou; et al. (Drug Delivery and Translational Research, 2025)

Copper oxide nanoparticles disrupt lysosomal function and promote foam cell formation in RAW264.7 macrophages - Yilin Luo; Kun Zhang; Lejiao Mao; Meiling Tan; Xiaomei Dong; Na Li; Yuexing Zhou; Chengzhi Chen; Zhen Zou; Jun Zhang (Toxicology, 2025)

Rapid visual detection of glutathione in vegetables and distinguishing multiple sulfur-containing compounds by smartphone-assisted sensor based on calcined PPy@CuNi-ZIF-67 nanozyme with enhanced oxidase-like activity - Linchun Nie; Jiazhi Xia; Jiawei Liao; Na Liu; Meiling Xu; Dejing Meng; Wenjing Liu; Qingxiang Zhou; Chunmao Chen (Food Chemistry, 2025)

Divergent trends in vegetation greenness and resilience across China's forestry ecological engineering regions - Xinxin Fu; Zhenhong Li; Jiahao Ma; Meiling Zhou; Lili Chen; Jianbing Peng (Ecological Engineering, 2025)

Enhanced hydrogen storage performance of Mg(BH4)2 with in-situ generated TiO2 and TiH2 catalysts - Zhenxuan Ma; Jiaguang Zheng; Ao Xia; Qingbo Zhang; Meiling Lv; Cong Li; Panpan Zhou (Chemical Engineering Journal, 2025)

Revealing the key organelle in the pathophysiology and clinical applications of animal toxins: Mitochondria - Linfeng Wang; Jiahao Liu; Sheng Zhou; Jiaqi Sun; Meiling Liu; Jianqi Zhao; Lixia Cheng; Zejing Wen; Xiaowen Bi; Chunhong Huang (Toxicon, 2025)

Ecosystem resilience response to forest fragmentation in China: Thresholds identification - Xinxin Fu; Zhenhong Li; Jiahao Ma; Meiling Zhou; Lili Chen; Jianbing Peng (Journal of Environmental Management, 2025)

Sensitive measurement of polycyclic aromatic hydrocarbons based on strong enrichment from magnetic covalent organic framework before high performance liquid chromatography analysis - Guangyu Dong; Liushan Jiang; Linchun Nie; Jiawei Liao; Xiaodie Geng; Wenjing Liu; Dejing Meng; Meiling Xu; Na Liu; Qingxiang Zhou; Chunmao Chen (Journal of Environmental Chemical Engineering, 2025)

Spatiotemporal changes of vegetation in the northern foothills of Qinling Mountains based on kNDVI considering climate time-lag effects and human activities - Lili Chen; Zhenhong Li; Chenglong Zhang; Xinxin Fu; Jiahao Ma; Meiling Zhou; Jianbing Peng (Environmental Research, 2025)

Deep Learning Imaging-Based Reconstruction Improved the Image Quality of Synthetic High B-Value DWI for Prostate Lesion Detecting - Xiuxiu Zhou; Hanxiao Zhang; Song Jiang; Jiankun Dai; Lingling Gu; Pei Zhang; Ye Fu; Jie Shi; Xinyi Wan; Meiling Xu; Shiyuan Liu; Li Fan (Journal of Medical and Biological Engineering, 2025)

Microscale fluvial landscape evolution and its impacts on early human settlement at the Shangshan cultural site in the upper Qiantang region, eastern China - Wenjia Zhang; Zhou Lin; Guoping Zhang; Leping Jiang; Meiling Chen; Shengchao Zhou; Yuchen Zhang; Xiang Zhao (Geomorphology, 2025)

Thresholding Dolphin Whistles Based on Signal Correlation and Impulsive Noise Features Under Stationary Wavelet Transform - Xiang Zhou; Ru Wu; Wen Chen; Meiling Dai; Peibin Zhu; Xiaomei Xu (Journal of Marine Science and Engineering, 2025)
The time–frequency characteristics of dolphin whistle signals under diverse ecological conditions and during environmental changes are key research topics that focus on the adaptive and response mechanisms of dolphins to the marine environment. To enhance the quality and utilization of passive acoustic monitoring (PAM) recorded dolphin whistles, the challenges faced by current wavelet thresholding methods in achieving precise threshold denoising under low signal-to-noise ratio (SNR) are confronted. This paper presents a thresholding denoising method based on stationary wavelet transform (SWT), utilizing suppression impulsive and autocorrelation function (SI-ACF) to select precise thresholds. This method introduces a denoising metric ρ, based on the correlation of whistle signals, which facilitates precise threshold estimation under low SNR without requiring prior information. Additionally, it exploits the high amplitude and broadband characteristics of impulsive noise, and utilizes the multi-resolution information of the wavelet domain to remove impulsive noise through a multi-level sliding window approach. The SI-ACF method was validated using both simulated and real whistle datasets. Simulated signals were employed to evaluate the method’s denoising performance under three types of typical underwater noise. Real whistles were used to confirm its applicability in real scenarios. The test results show the SI-ACF method effectively eliminates noise, improves whistle signal spectrogram visualization, and enhances the accuracy of automated whistle detection, highlighting its potential for whistle signal preprocessing under low SNR.

Facile solvothermal synthesis of ultrafine platinum nanowires on carbon nanotubes to enhance hydrogen evolution performance - Chang-An Zhou; Meiling Ran; Huixi Chen; Tingting Ma; Chunhui Wu; Hong Zhang; Lei Song; Chao Wang; Kui Ma; Hairong Yue (Fuel, 2025)

Birnessite enhanced Cr(III) oxidation during subsurface geochemical processes: Role of Mn(III)-induced nonphotochemical reactive oxygen species - Yuting Zhou; Chuling Guo; Yanping Deng; Yanjun Jiang; Meiling Yin; Kai Chen; Siyu Zhang; Guining Lu; Zhi Dang (Environmental Pollution, 2025)

Abnormal sensory processing cortex in insomnia disorder: a degree centrality study - Hui Wang; Haining Li; Ziyi Liu; Chiyin Li; Zhaoyao Luo; Wei Chen; Meiling Shang; Huiping Liu; Fatemeh Naderi Nejad; Yuanping Zhou; Ming Zhang; Yingxiang Sun (Brain Imaging and Behavior, 2025)

Effects of coexisting goethite or lepidocrocite on Fe(II)-induced ferrihydrite transformation pathways and Cd speciation - Meiling Yin; Xin Li; Chuling Guo; Qiaohui Zhong; Xiaofei Li; Lijuan Zeng; Yuting Zhou; Chen Yang; Zhi Dang (Science of The Total Environment, 2025)

Dual-mode detection of human immunoglobulin via copper oxide nanozyme catalysis fluorescent species generation and photoelectrochemical alteration in ZnIn2S4/SnO2-based system - Jiawei Zhou; Lili Zhao; Yuee Zhong; Peipei Li; Xiaohua Zhu; Shu Huang; Youyu Zhang; Meiling Liu (Analytica Chimica Acta, 2025)

MicroRNA expression profiles in plasma exosomes of late pregnant giant pandas - Meiling Cheng; Yingmin Zhou; Qian Wang; Bo Luo; Yanwu Lai; Jianbin Cheng; Xiuyue Zhang; Yan Huang; Desheng Li (Molecular Biology Reports, 2024)

A close-looped DNAzyme walker with an available catalytic domain for electrochemiluminescent detection of acetamiprid - Lidan Zhao; Meiling Zhao; Xuemei Zhou; Ruo Yuan; Xia Zhong; Ying Zhuo (Food Chemistry, 2024)

Development of multi-cross-linking, rapid curing, and easy cleaning, edible hydrogels for meat preservation - Yuxin Cheng; Jiaxin Xu; Rongfan Zhang; Jianguo Lin; Meiling Zhou; Xianmin Qin; Keshan Wang; Ying Zhou; Qiujin Zhu; Yongguo Jin; Yuanyuan Liu (Food Hydrocolloids, 2024)

Enhanced oxygen anions generation on Bi2S3/Sb2S3 heterostructure by visible light for trace H2S detection at room temperature - Meiling Yu; Jiayu Li; Dongmin Yin; Zhenze Zhou; Chenda Wei; You Wang; Juanyuan Hao (Journal of Hazardous Materials, 2024)

Occupation patterns during the Shangshan in the upper Qiantang River Basin, eastern China: A geomorphic study based on GIS - Wenjia Zhang; Zhou Lin; Leping Jiang; Chao Ding; Meiling Chen; Shengchao Zhou; Xiang Zhao (Quaternary International, 2024)

Dynamic response of sloping seabed with buried twin pipelines under wave loading - Fan Meiling; Duan Lunliang; Zhou Jianting; Liu Zhuang; Wang Duoyin (Ocean Engineering, 2024)

Cellulose nanofibrils-stabilized food-grade Pickering emulsions: Clarifying surface charge's contribution and advancing stabilization mechanism understanding - Yadong Zhao; Feifan Zhang; Meiling Chen; Fei Liu; Bin Zheng; Wenhua Miao; Huimin Gao; Rusen Zhou (Food Hydrocolloids, 2024)

Microbial role in enhancing transfer of straw-derived nitrogen to wheat under nitrogen fertilization - Shuyu Huang; Xue Gao; Li Zeng; Meiling Zhang; Liyu Zhang; Shiyu Wang; Yuanzheng Zhao; Wei Zhou; Chao Ai (Soil and Tillage Research, 2024)

Surface properties of schwertmannite with different sulfate contents and its effect on Cr(VI) adsorption - Chaoping Wang; Kai Chen; Meiling Yin; Yuting Zhou; Qinglin Zhuang; Qianqian Cao; Zhi Dang; Chuling Guo (Geochimica et Cosmochimica Acta, 2024)

Microbial features with uranium pollution in artificial reservoir sediments at different depths under drought stress - Siyu Liu; Juan Liu; Jingye She; Zhenyu Xie; Lei Zhou; Qunwei Dai; Xing Zhang; Yuebing Wan; Meiling Yin; Xinjiao Dong; Min Zhao; Diyun Chen; et al. (Science of The Total Environment, 2024)

Source appointment of δ13C in sediments of a maar lake in southern China: Implications of fossil fuel CO2 emissions - Meiling Guo; Yongming Han; Weiguo Liu; Yunning Cao; Dewen Lei; Weijian Zhou; Zhisheng An (Applied Geochemistry, 2024)

Utilizing different types of biomass materials to modify steel slag for the preparation of composite materials used in the adsorption and solidification of Pb in solutions and soil - An Wang; Meiling Wu; Zhongyuan Li; Yuqiang Zhou; Fanmin Zhu; Zhanbin Huang (Science of The Total Environment, 2024)

Illuminated fulvic acid stimulates denitrification and As(III) immobilization in flooded paddy soils via an enhanced biophotoelectrochemical pathway - Yanqiong Zeng; Honghui Wang; Jiehua Hu; Jing Zhang; Feng Wang; Tongyu Wang; Qiqi Zhou; Randy A. Dahlgren; Meiling Gao; Hui Gao; Zheng Chen (Science of The Total Environment, 2024)

A Fe-Ni-MOF-74@bamboo photothermal evaporator for efficient solar steam generation - Yiduo Chen; Dongxu Gu; Yujuan Zhao; Chaowei Zhang; Meiling Li; Qi Zhou; Yonghui Lin; Yaru Gong; Zhongmin Su; Weiting Yang (Desalination, 2024)

Microbial ecological clusters structured by environments drive maize residue decomposition at the continental scale - Meiling Zhang; Shiyu Wang; Liyu Zhang; Wentao Li; Mengmeng Cao; Shuyu Huang; Xinpeng Xu; Ping He; Wei Zhou; Laurent Philippot; Chao Ai (Science of The Total Environment, 2023)

Synthesis of MnOOH-hydroxyapatite nanowires for degradation of tetracycline - Shenglan Zhao; Meiling Zhou; Jiarui Ren; Yaping Zhang; Yufeng He; Rongmin Wang (Journal of Environmental Chemical Engineering, 2023)

Bilobetin attenuates Staphylococcus aureus virulence by targeting Von Willebrand factor-binding protein and staphylocoagulase - Chongling Zhang; Wenyuan Zhang; Shuyue Zhu; Chunjie Hu; Sihua Che; Meiling Wang; Mengli Jin; Nan Bian; Wu Song; Shuang Jiang; Yijing Jiang; Juan Hou; et al. (World Journal of Microbiology and Biotechnology, 2023)

Nanocomposite hydrogel to deliver the immunomodulator lenalidomide and anti-inflammatory hesperidin locally to joints affected by rheumatoid arthritis - Xingjie Du; Yan Lin; Zheyu Shuai; Junfeng Duan; Changguang Wang; Junsheng Liu; Jun Jiang; Jianming Wu; Meiling Zhou; Zhirong Zhang; Zhongbing Liu; Xiangyu Zhou; et al. (Chemical Engineering Journal, 2023)

Investigating the effects of organic amendments on soil microbial composition and its linkage to soil organic carbon: A global meta-analysis - Jiwen Cui; Binggeng Yang; Meiling Zhang; Dali Song; Xinpeng Xu; Chao Ai; Guoqing Liang; Wei Zhou (Science of The Total Environment, 2023)

Experimental and mechanistic study on the removal of lead from solution by sulfuric acid modified steel slag adsorbent - An Wang; Meiling Wu; Zhongyuan Li; Yuqiang Zhou; Zhanbin Huang (Journal of Environmental Chemical Engineering, 2023)

Structure regulation of two-dimensional composites facilitates solar/electric desalination - Xiaoran Cheng; Chenyang Xing; Weifeng Liu; Meiling Wang; Xuguang Liu; Jiadong Zhou (Chemical Engineering Journal, 2023)

Numerical study of regular wave-induced oscillatory soil response during the caisson installation - Lunliang Duan; Chenxi Qin; Jianting Zhou; Guangwu Tang; Duoyin Wang; Meiling Fan (Ocean Engineering, 2023)

Development and Characterization of Multifunctional Wound Dressing with the Property of Anti-bacteria and Angiogenesis - Xi He; Meiling Zhou; Xuemei Chen; Jing Wang; Xiaoli Zhao; Yanxia Zhu; Tao Liu (Probiotics and Antimicrobial Proteins, 2023)

Subducted carbonates not required: Deep mantle melting explains stable Ca isotopes in kimberlite magmas - Michael A. Antonelli; Andrea Giuliani; Zaicong Wang; Meiling Wang; Lian Zhou; Lanping Feng; Ming Li; Zhaofeng Zhang; Fang Liu; Russell N. Drysdale (Geochimica et Cosmochimica Acta, 2023)

Electrooxidation of methane to acetic acid over ZnO nanosheets: Defect-sites engineering - Mingming Luo; Jiayao Li; Meiling Wang; Yongqing Ma; Ganhong Zheng; Min Wang; Yitong Zhou (Journal of Environmental Chemical Engineering, 2023)

Pharmacokinetics and residue elimination of metalaxyl enantiomers in snakehead (Channa argus) - Hao Zhou; Meiyu Zhang; Qi Shan; Heqing Huang; Meiling Zhang; Shugui Liu; Jiawei Lin; Lisha Ma; Guangming Zheng; Lichun Li; Cheng Zhao; Xiaoxin Dai; et al. (Aquaculture, 2023)

Self-intercepting interference of hydrogen-bond induced flexible hybrid film to facilitate lithium extraction - Meiling Wang; Tianyuan Zhang; Zhixiang Meng; Chongji Wang; Weikang Dong; Jijian Liu; Su Yang; Xudong Hou; Xiaoran Cheng; Weifeng Liu; Chenyang Xing; Xuguang Liu; et al. (Chemical Engineering Journal, 2023)

Rapamycin ameliorates brain damage and maintains mitochondrial dynamic balance in diabetic rats subjected to middle cerebral artery occlusion - Changchun Hei; Yujia Zhou; Chenyang Zhang; Furong Gao; Meiling Cao; Shilin Yuan; Yixin Qin; P. Andy Li; Xiao Yang (Metabolic Brain Disease, 2023)

A highly-stretchable and adhesive hydrogel for noninvasive joint wound closure driven by hydrogen bonds - Hongsheng Liu; Xiaole Hu; Wen Li; Meiling Zhu; Jinhuan Tian; Lihua Li; Binghong Luo; Changren Zhou; Lu Lu (Chemical Engineering Journal, 2023)

Correction to: Construction of HAnW‑based nanotwigs for removing inorganic fluorion in wastewater - Meiling Zhou; Hua Yang; Zejun Wang; Jiarui Ren; Rongmin Wang; Yufeng He (Environmental Science and Pollution Research, 2022)

Construction of HAnW-based nanotwigs for removing inorganic fluorion in wastewater - Meiling Zhou; Hua Yang; Zejun Wang; Jiarui Ren; Rongmin Wang; Yufeng He (Environmental Science and Pollution Research, 2022)

Comparative analysis of microsatellites in coding regions provides insights into the adaptability of the giant panda, polar bear and brown bear - Meiling Cheng; Daxin Xie; Megan Price; Chuang Zhou; Xiuyue Zhang (Genetica, 2022)

Construction of WO3 nanocubes@Loess for rapid photocatalytic degradation of organics in wastewater under sunlight - Hua Yang; Peiyu Cao; Yaping Zhang; Meiling Zhou; Qianqian Wang; Rongmin Wang; Pengfei Song; Yufeng He (Environmental Science and Pollution Research, 2022)

Antibacterial Activities of Peptide HF-18 Against Helicobacter pylori and its Virulence Protein CagA - Chenyu Zhou; Meiling Jiang; Xinyue Ye; Xiaoyun Liu; Wenxuan Zhao; Lingman Ma; Changlin Zhou (International Journal of Peptide Research and Therapeutics, 2022)

Quality Study of the Preparation of Virgin Brown Sugar Powder by Vacuum Drying - Yuchao Dai; Mingxing Li; Meiling Li; Zhuolin Wang; Jie Lu; Yiyang Zhou; Wenping Meng; Shufang Chen; Qingtao Li (Sugar Tech, 2021)

A new parametric segmentation method based on sandy mudstone SEM images - Meiling Zhou; Jianlin Li; Weijie Xu; Feng Xu; Eleyas Assefa; Huafeng Deng (Arabian Journal of Geosciences, 2021)

Brain Dicer1 Is Down-Regulated in a Mouse Model of Alzheimer’s Disease Via Aβ42-Induced Repression of Nuclear Factor Erythroid 2-Related Factor 2 - Yan Wang; Meiling Lian; Jing Zhou; Shengzhou Wu (Molecular Neurobiology, 2020)

Analysis of flavonoids and anthocyanin biosynthesis-related genes expression reveals the mechanism of petal color fading of Malus hupehensis (Rosaceae) - Meiling Han; Chen Yang; Jing Zhou; Jiabin Zhu; Jiaxin Meng; Ting Shen; Zhuanxia Xin; Houhua Li (Brazilian Journal of Botany, 2020)

Investigation of Lactic Acid Bacteria Isolated from Giant Panda Feces for Potential Probiotics In Vitro - Qian Liu; Xueqin Ni; Qiang Wang; Zhirong Peng; Lili Niu; Meiling Xie; Yicen Lin; Yi Zhou; Hao Sun; Kangcheng Pan; Bo Jing; Dong Zeng (Probiotics and Antimicrobial Proteins, 2019)

Important interaction of chemicals, microbial biomass and dissolved substrates in the diel hysteresis loop of soil heterotrophic respiration - Qing Wang; Nianpeng He; Yuan Liu; Meiling Li; Li Xu; Xuhui Zhou (Plant and Soil, 2018)

Characterization of a novel dsRNA mycovirus isolated from strain A105 of Rhizoctonia solani AG-1 IA - Meiling Zhang; Li Zheng; Chen Liu; Canwei Shu; Erxun Zhou (Archives of Virology, 2018)

Molecular cloning and expression analysis of major intrinsic protein gene in Chlamydomonas sp. ICE-L from Antarctica - Lulu Li; Meiling An; Changfeng Qu; Zhou Zheng; Yibin Wang; Fangming Liu; Yingying He; Xiaodong He; Jinlai Miao (Extremophiles, 2017)

A glucuronokinase gene in Arabidopsis, AtGlcAK, is involved in drought tolerance by modulating sugar metabolism - Wenjun Xiao; Shuai Hu; Xiaoxun Zhou; Runyu Yao; Jingru Luo; Congying Yuan; Hongping Chang; Cheng Zhang; Ji Huang; Jinyan Li; Shucan Liu; Meiling Li; et al. (Plant Molecular Biology Reporter, 2017)

Biomass, nutrient uptake and fatty acid composition of Chlamydomonas sp. ICE-L in response to different nitrogen sources - Meiling An; Yibin Wang; Fangming Liu; Xiaoqing Qi; Zhou Zheng; Naihao Ye; Chengjun Sun; Jinlai Miao (Acta Oceanologica Sinica, 2017)

Estimation of residue depletion of cyadox and its marker residue in edible tissues of pigs using physiologically based pharmacokinetic modelling - Lingli Huang; Zhoumeng Lin; Xuan Zhou; Meiling Zhu; Ronette Gehring; Jim E. Riviere; Zonghui Yuan (Food Additives & Contaminants: Part A, 2015)

Two distinct classes of protein related to GTB and RRM are critical in the sclerotial metamorphosis process of Rhizoctonia solani AG-1 IA - Canwei Shu; Jieling Chen; Si Sun; Meiling Zhang; Chenjiaozi Wang; Erxun Zhou (Functional & Integrative Genomics, 2015)

The complete genomic sequence of a novel mycovirus from Rhizoctonia solani AG-1 IA strain B275 - Li Zheng; Huiquan Liu; Meiling Zhang; Xiong Cao; Erxun Zhou (Archives of Virology, 2013)

Genome-wide identification, classification, and expression analysis of CDPK and its closely related gene families in poplar (Populus trichocarpa) - Ran Zuo; Ruibo Hu; Guohua Chai; Meiling Xu; Guang Qi; Yingzhen Kong; Gongke Zhou (Molecular Biology Reports, 2013)

In vitro evaluation of a mammary gland specific expression vector encoding recombinant human lysozyme for development of transgenic dairy goat embryos - Tao Gui; Meiling Zhang; Jianwen Chen; Yuanliang Zhang; Naru Zhou; Yu Zhang; Jia Tao; Liucai Sui; Yunsheng Li; Ya Liu; Xiaorong Zhang; Yunhai Zhang (Biotechnology Letters, 2012)